Exercising The State’s Right of Preemption to The Alienation of Historical Monuments - Chiriac, Natalia; Bostan, Ina; Ursu, Viorica (Technium Social Sciences Journal, 2022)
Known since ancient times, the legal regime of the right of preemption has undergone a surprising evolution. This right will be recognized among the institutions that enjoy a general legislative consecration and the modernized Civil Code. Thus, the legal provisions regarding the institution of the right of preemption have been essentially reformed, taking into account the deficiencies found in the special legislation, or at the current stage, we encounter different species of the right of preemption in the most varied fields, such as cultural, commercial, privatization, intellectual property, etc. In this regard, we set out to analyze the right of preemption in the cultural field through this scientific approach. Due to the importance of the goods to be alienated, it was felt necessary to clarify specific regulations, taking into account the exercise of this right, showing the reason for which it was instituted; the procedure or conditions under which it is exercised; the sanction that intervenes in case of non-compliance, as well as the consequences of applying this sanction.